Epidemiology of secondary school boys' and girls' basketball injuries: National athletic treatment, injury and outcomes network - Allen, A. N.; Wasserman, E. B.; Williams, R. M.; Simon, J. E.; Dompier, T. P.; Kerr, Z. Y.; Snyder Valier, A. R. (Journal of Athletic Training, 2019)
Context. Little is known about non-time-loss (NTL) injury patterns in basketball athletes. Knowledge of these patterns may aid in the development of prevention and management strategies for patients with these injuries.